2005
DOI: 10.1007/s10509-005-1195-6
|View full text |Cite
|
Sign up to set email alerts
|

Energy distribution of a stringy charged black hole

Abstract: Abstract. The energy distribution associated with a stringy charged black hole is studied using Møller's energy-momentum complex. Our result is reasonable and it differs from that known in literature using Einstein's energymomentum complex.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 16 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…The only differences are 1. The gravitational energy, using Møller's prescription [4], depends on the mass parameter M and on the charge Q (see Gad [5]), while in the Schwarzschild black hole is given only by the mass parameter M (see Xulu [6]). …”
Section: Introductionmentioning
confidence: 99%
“…The only differences are 1. The gravitational energy, using Møller's prescription [4], depends on the mass parameter M and on the charge Q (see Gad [5]), while in the Schwarzschild black hole is given only by the mass parameter M (see Xulu [6]). …”
Section: Introductionmentioning
confidence: 99%
“…Gad, has investigated energy-momentum densities of a general static axially symmetric vacuum space-time, with the help of Landau-Lifshitz and Bergmann-Thomson energy-momentum complexes and found that these two definitions of energy momentum complexes do not provide the same energy density for the space-time (Gad 2006a(Gad , 2006b. However, M. Gad using the energy-momentum complexes of Einstein and Papapetrou calculated energy-momentum density of Weyl metric as well as Curzon metric and has showed that these two different definitions of energy-momentum complexes do not provide the same energy density for Weyl metric, although they give the same momentum density (Gad 2004a(Gad , 2004b(Gad , 2004c. Many researchers considered different energy-momentum complexes and obtained encouraging results (Radinschi and Grammenos 2006;Yang and Radinschi 2004;Sharif 2002Sharif , 2003Sharif , 2004aSharif , 2004bVagenas 2003aVagenas , 2003bVagenas , 2004Gad 2004aGad , 2004bGad , 2004cGad , 2006aGad , 2006b.…”
Section: Introductionmentioning
confidence: 99%
“…These results agree for the Schwarzschild, Vaidya and Janis-Newmann-Winicour space-times, but disagree for the Reissner-Nordström space-time. Many authors had similarly successfully applied the aforementioned energy-momentum complexes to various black hole configurations (Gad 2004a(Gad , 2004b(Gad , 2005a(Gad , 2006a(Gad , 2006b(Gad , 2006cVagenas 2003aVagenas , 2003bVagenas , 2004Vagenas , 2005Vagenas , 2006Yang et al 1997;Radinschi 1999Radinschi , 2000aRadinschi , 2000bRadinschi , 2000cRadinschi , 2000dRadinschi , 2000e, 2001aRadinschi , 2001bRadinschi , 2001cRadinschi , 2005Yang and Radinschi 2002, 2004Radinschi and Yang 2005;Radinski and Grammenos 2006;Yang 2000;Salti 2005, 2006;Salti 2005aSalti , 2005bSalti , 2005cSalti and Havare 2005;Havare et al 2006;Patashnick 2005;Grammenos 2005). …”
Section: Introductionmentioning
confidence: 99%